2016
DOI: 10.3389/fpls.2016.00358
|View full text |Cite
|
Sign up to set email alerts
|

A Fusion between Domains of the Human Bone Morphogenetic Protein-2 and Maize 27 kD γ-Zein Accumulates to High Levels in the Endoplasmic Reticulum without Forming Protein Bodies in Transgenic Tobacco

Abstract: Human Bone Morphogenetic Protein-2 (hBMP2) is an osteoinductive agent physiologically involved in bone remodeling processes. A commercialized recombinant hBMP2 produced in mammalian cell lines is available in different clinical applications where bone regeneration is needed, but widespread use has been hindered due to an unfavorable cost/effective ratio. Protein bodies are very large insoluble protein polymers that originate within the endoplasmic reticulum by prolamine accumulation during the cereal seed deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…These results are in accordance with a previous study which showed that, unlike zeolin-Nef that formed PBs, zein-Nef did not efficiently form PBs and could not be distinguished from the ER (de Virgilio et al, 2008). Zein-rhBMP2ad also did not form protein bodies but was retained in the ER (Ceresoli et al, 2016). Our findings present another case where Zera R -tagged gp140 did not efficiently form PBs but was associated with the ER, thereby separating and settling in fractions of densities previously noted where ER membrane fragment settles.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are in accordance with a previous study which showed that, unlike zeolin-Nef that formed PBs, zein-Nef did not efficiently form PBs and could not be distinguished from the ER (de Virgilio et al, 2008). Zein-rhBMP2ad also did not form protein bodies but was retained in the ER (Ceresoli et al, 2016). Our findings present another case where Zera R -tagged gp140 did not efficiently form PBs but was associated with the ER, thereby separating and settling in fractions of densities previously noted where ER membrane fragment settles.…”
Section: Discussionsupporting
confidence: 93%
“…The authors did not think the failure to form PBs was due to misfolding that could be caused by the possible aberrant disulfide bridges (hBMP2ad contains 7 Cys residues). Instead, they reasoned that the failure of zein-rhBMP2ad to form PBs may have been due to N-glycosylation that increased the solubility of rhBMP2ad and prevented PB formation (Ceresoli et al, 2016). We note that gp140 contains ≈28 N-glycosylation sites which could favor solubility of the Zera R -tagged gp140, thus preventing optimal assembly into PBs.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…27 kD γ-zein is composed of an N-terminal domain characterized by eight repeats of the amphipathic sequence ValHisLeuProProPro and seven Cys residues, followed by a C-terminal 8CM/ABC domain. The N-terminal domain promotes PB formation when fused to other proteins that are otherwise available for intracellular traffic ( Mainieri et al, 2004 ; Llop-Tous et al, 2010 ), although this dominant effect is not universal ( de Virgilio et al, 2008 ; Ceresoli et al, 2016 ). Deletion of the N-terminal domain from γ-zein causes secretion of the remaining ABC domain, and the reciprocal deletion causes ER retention of the N-terminal domain, although in this case the typical round-shaped PBs are not formed ( Geli et al, 1994 ).…”
Section: Maizementioning
confidence: 99%